Konsep Etika Lingkungan Menurut Seyyed Hossein Nasr: Respon terhadap Krisis Ekologi - Yudistira Ananda Setiadi; Humaidi Humaidi (Pusat Riset dan Inovasi Nasional, 2026)
The current global environmental crisis is not only caused by technical and economic factors, but also reflects a spiritual and ethical crisis in the modern human view of nature. Seyyed Hossein Nasr, a contemporary Islamic philosopher and thinker, offers an environmental ethics approach based on Islamic spirituality that emphasizes the sanctity of nature and the relationship between humans and God as the center of ecological morality. This study aims to examine in depth the concept of environmental ethics according to Nasr, as well as its relevance in responding to contemporary ecological challenges. Using a qualitative descriptive approach and literature study of Nasr's works, this study found that Nasr's concept of environmental ethics is based on the principles of monotheism, trust, and the ontological relationship between humans and the universe. Nasr criticized the Western secular and anthropocentric paradigm that objectifies nature and called for the restoration of the sacred relationship between humans and the environment as the basis for sustainable ecological ethics. The results of this study are expected to contribute to the development of holistic and spiritual environmental ethics in global and local contexts.